Compensatory changes in degenerating spinal motoneurons sustain functional sparing in the SOD1‐G93A mouse model of amyotrophic lateral sclerosis. Issue 2 (7th August 2019) - Giusto, Elena; Codrich, Marta; de Leo, Gioacchino; Francardo, Veronica; Coradazzi, Marino; Parenti, Rosalba; Gulisano, Massimo; Vicario, Nunzio; Gulino, Rosario; Leanza, Giampiero
Abstract: Plastic changes have been reported in the SOD1‐G93A mouse model of amyotrophic lateral sclerosis, a disorder characterized by progressive motoneuronal loss; however, whether these changes related with the onset and development of motor impairments is still unclear. Here, the functional and anatomical changes taking place in SOD1‐G93A mice and their time course were investigated during ongoing motoneuronal degeneration. Starting from about 4 postnatal weeks, SOD1‐G93A and wild‐type (WT) mice were evaluated in the rotarod test, to be sacrificed at about 12–13 or 19 weeks of age, and their lumbar spinal cords were processed for histo‐ and immunohistochemistry. Compared to age‐matched WT controls, 12 weeks‐old SOD1‐G93A mice exhibited relatively mild or no motor impairments in the rotarod test, in spite of a dramatic (≈60%, as estimated by stereology) loss of choline acetyl‐transferase (ChAT)‐immunoreactive motoneurons which remained virtually unchanged in SOD1‐G93A mice surviving up to 19 weeks. Notably, the functional sparing in SOD1‐G93A mice at 12 weeks was paralleled by a marked ≈50% increase in motoneuron volume and a near‐normal density of acetylcholinesterase‐positive process arborization, which was significantly increased when analyzed as ratio to the decreased number of ChAT‐positive motoneurons. By contrast, at 19 weeks, when motor deficits had become dramatically evident, both measures were found reverted to about 50–60% of control values. Thus, at specific stages during the progression of the disease, robust compensatory events take place in surviving motoneurons of SOD1‐G93A mice, which sustain motor performance, and whose full understanding may highlight a valuable therapeutic opportunity window. Abstract : In presymptomatic, 12–13 week‐old, SOD1‐G93A mice, virtually intact motor performance was detected in spite of ≈60% motoneuron loss in the lumbar spinal cord. This functional sparing was seen associated to a marked increase in motoneuronal volume and fairly normal proximal cholinergic fiber density, which however appeared dramatically altered at 19 weeks, when motor abilities became strongly disrupted. At this latter timepoint, no changes in motoneuron numbers were detected, suggesting that robust compensatory events take place in surviving motoneurons of SOD1‐G93A mice, which sustain motor performance and may highlight a valuable therapeutic opportunity window.